2013
DOI: 10.1002/wrcr.20376
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic conductivity fields: Gaussian or not?

Abstract: Hydraulic conductivity (K) fields are used to parameterize groundwater flow and transport models. Numerical simulations require a detailed representation of the K field, synthesized to interpolate between available data. Several recent studies introduced high resolution K data (HRK) at the Macro Dispersion Experiment (MADE) site, and used ground-penetrating radar (GPR) to delineate the main structural features of the aquifer. This paper describes a statistical analysis of these data, and the implications for K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 57 publications
0
22
0
Order By: Relevance
“…In applications, a fractional difference is applied to a time series data set, and the order α of the fractional difference is chosen to remove long range correlations from the data. See [50] for a recent application to ground water hydrology.…”
Section: Artfima Modelmentioning
confidence: 99%
“…In applications, a fractional difference is applied to a time series data set, and the order α of the fractional difference is chosen to remove long range correlations from the data. See [50] for a recent application to ground water hydrology.…”
Section: Artfima Modelmentioning
confidence: 99%
“…Investigation of when functions will satisfy self similarity relationships, which gives insight into the applicable extent of scaling transformations and the regimes in which multi-scale models must be developed for a particular problem. Particularly for hydrological phenomena, investigations have concluded that certain medium and fluid parameters, such as the hydraulic conductivity, undergo fundamental changes in their distribution as the scale increases from the pore scale to the watershed scale (and above) (Kavvas, 1999;Meerschaert et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In this domain as well, however, increased computer power has led to the use of finer resolution models but mostly in hypothetical virtual reality simulations to explore the impacts of subsurface heterogeneities on flow and transport processes. This type of study also has a long history, from the early random field experiments of Freeze (1975Freeze ( , 1980, Smith and Schwarz (1980) and Smith and Hebbert (1979) to the recent multimillion element simulations of, for example, Zinn et al (2003), Feyen et al (2006), Michael et al (2010), Guilleminot et al (2012), and Meerschaert et al (2013).…”
Section: Hyperresolution Informationmentioning
confidence: 97%